(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2020)
The words “national minorities” have not always been part of Russian and Ukrainian Constitutions. Starting from this assumption, this essay aims to verify - from a diachronic and synchronic comparative perspective - whether the introduction of those words in different historical phases led to a significant dissimilarity in the way the two countries developed their respective legal regulation on national minorities, or if, in spite of that, they still elaborated a similar one.